ON g*Î±-I-CONTINUOUS IN TOPOLOGICAL SPACES - Indirani, K. (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
In this paper we introduce and study the notions of g*Î±-I-closed sets and g*Î±-I-continuity in Ideal topological spaces